Assessing Needs for Quality Improvement: A Study of Nature-Based Education Principles (Sekolah Alam Way) at Saga Lifeschool, Indonesia - Robianti, Febi; Raufu, Mufutau; Sasongko, Marsahid; Sikirat Abolanle Busari-Raufu; Raufu, Jemilat; Yamani, Khalila (Jurnal Pendidikan Non formal, 2024)
Nature-based education offers a transformative approach to sustainable education by integrating natural environments and sustainability principles into active learning experiences. In Indonesia, Saga Lifeschool, along with over 200 nature-based schools under Jaringan Sekolah Alam Nusantara (JSAN), exemplifies this model through its "Sekolah Alam Way" (SA WAY) system. This system emphasizes holistic education aligned with sustainable development goals and the core values of Pancasila, including environmental stewardship, community spirit, and global diversity appreciation. This research aims to assess the quality improvement needs in SA WAY’s implementation of nature-based education, focusing on enhancing educational practices that promote academic, ethical, social, and environmental growth. The study applies theories such as experiential learning, place-based education, and embodied cognition to evaluate how hands-on activities—such as outdoor projects, environmental conservation, and community engagement—support cognitive, ethical, and social development. Findings indicate that while SA WAY effectively instills these values, improvements in resources, teacher training, and outdoor learning infrastructure are needed to further enhance educational quality and sustainability. The research highlights the importance of continuous development in these areas to ensure the long-term success of nature-based education and its alignment with sustainable practices.